Vodenje in diagnosticiranje curka naelektrenih delcev - Paulin, Alojz (Vakuumist, 1998)
Particle accelerators operating depends first of all on particle beam generation and on high vacuum establishing but the supervisor system has to assure also the geometrical control beam shape and trevelling along the central trajectoria in working tube. This is usually made by slits and slots or for charged particles by appointable magnetic fields (diquadro- and sextu- pols). For automatic mistake removal, an information is needed on beam data parameters. To collect mentioned data several sensors are built in acceleratortube walls. The contribution represents some principles for detection of beam position and intensity which can be studied, realized and tested with our facilities.
Keywords: vakuumska tehnika; Electronika; elektronika; pospeševalniki; curek delcev